The power of identity: Midwives 'with woman' - Bradfield, Zoe; Hauck, Yvonne; Duggan, Ravani; Kelly, Michelle (ELSEVIER, 2019)
Background: Being ‘with woman’ is a fundamental construct of the midwifery profession, inherent in professional standards and philosophy statements around the world. Despite its centrality, very little research has been undertaken to explore the phenomenon.